Pengaruh Pembelajaran Berbasis Blended Learning Terhadap Literasi Sains Siswa Pada Materi Perpindahan Kalor - Gustiana, Rina; Jayadinata, Asep Kurnia; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2019)
Education requires innovation to be able to compete with other countries, one of which is in the field of scientific literacy. This study was conducted to determine the increase in scientific literacy of class V students of heat transfer material through blended learning. The research method used is a quasi-experiment that compares two different groups of classes. The design used is nonequivalent control group design or the presence of a control and experimental group. Cijambe I Elementary School as a control group using offline blended learning and Cijambe II Elementary School as an experimental group using online blended learning. The findings are that the increase in scientific literacy of students in the experimental class is higher than the control class, this is evidenced by the difference in the average in the control class is lower than the experiment. The value of the difference in the average experimental class was 16.94 while the control class was 0.93. The improvement of students' scientific literacy skills in heat transfer material through online blended learning compared to offline.